Crucial Conversations: An interprofessional learning opportunity for senior healthcare students. Issue 6 (1st November 2016) - Delisle, Megan; Grymonpre, Ruby; Whitley, Rebecca; Wirtzfeld, Debrah
ABSTRACT: Clinical errors due to human mistakes are estimated to result in 400, 000 preventable deaths per year. Strategies to improve patient safety often rely on healthcare workers' ability to speak up with concerns. This becomes difficult during critical decision-making as a result of conflicting opinions and power differentials, themes underrepresented in many interprofessional initiatives. These elements are prominent in our interprofessional initiative, namely Crucial Conversations. We sought to evaluate this initiative as an interprofessional learning (IPL) opportunity for pre-licensure senior healthcare students, as a way to foster interprofessional collaboration, and as a method of empowering students to vocalise their concerns. The attributes of this IPL opportunity were evaluated using the Points for Interprofessional Education Score (PIPES). The University of the West of England Interprofessional Questionnaire was administered before and after the course to assess changes in attitudes towards IPL, relationships, interactions, and teamwork. Crucial Conversations strongly attained the principles of interprofessional education on the PIPES instrument. A total of 38 volunteers completed the 16 hours of training: 15 (39%) medical rehabilitation, 10 (26%) medicine, 7 (18%) pharmacy, 5 (13%) nursing, and 1 (2%) dentistry. Baseline attitude scores were positive for three of the four subscales, all of which improved post-intervention. Interprofessional interactions remained negative possibly due to the lack of IPL opportunities along the learning continuum, the hidden curriculum, as well as the stereotyping and hierarchical structures in today's healthcare environment preventing students from maximising the techniques learned by use of this interprofessional initiative.